2011
DOI: 10.1515/astro-2017-0317
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Broad Absorption Line Profiles in a Sample of QSO Spectra

Abstract: Most of the Broad Absorption Lines (BALs) in quasars show very complex profiles. An idea to explain these profiles is that the dynamical systems of broad line regions are not homogeneous but consist of a number of dense regions or ion populations with different physical parameters. This approach is used to study the ultraviolet CIV resonance lines in the spectra of a group of high ionization BAL quasars, using the Gauss-Rotation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…It should be noted that the model (Danezis et al 2003(Danezis et al , 2007Lyratzi et al 2007) has been used to resolve broad absorption profiles, of transitions such as C IV Si IV, Mg II, N V, into multiple narrow components in the case of hot emission stars (see, Danezis et al 2003Danezis et al , 2007Danezis et al , 2009Lyratzi et al 2003Lyratzi et al , 2007Antoniou et al 2011aAntoniou et al , b, 2014 and references therein) as well as in the case of quasars (see, Lyratzi et al 2009Lyratzi et al , 2011Stathopoulos et al 2015, 2017 andreferences therein). To conclude, we note that in two previous papers (Stathopoulos et al 2015(Stathopoulos et al , 2017 we showed that Si IV and C IV BALs, in individual BALQSOs, consist of the same number of absorption components which is confirmed by the study of .…”
Section: Continuum Line Fitting and Goodness Of Fitmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that the model (Danezis et al 2003(Danezis et al , 2007Lyratzi et al 2007) has been used to resolve broad absorption profiles, of transitions such as C IV Si IV, Mg II, N V, into multiple narrow components in the case of hot emission stars (see, Danezis et al 2003Danezis et al , 2007Danezis et al , 2009Lyratzi et al 2003Lyratzi et al , 2007Antoniou et al 2011aAntoniou et al , b, 2014 and references therein) as well as in the case of quasars (see, Lyratzi et al 2009Lyratzi et al , 2011Stathopoulos et al 2015, 2017 andreferences therein). To conclude, we note that in two previous papers (Stathopoulos et al 2015(Stathopoulos et al , 2017 we showed that Si IV and C IV BALs, in individual BALQSOs, consist of the same number of absorption components which is confirmed by the study of .…”
Section: Continuum Line Fitting and Goodness Of Fitmentioning
confidence: 99%
“…Η μία περίπτωση είναι ότι οι BALs, είναι το προϊόν ενός ομαλού, συνεχούς και ομοιογενούς ανέμου (Scargle et al 1970, Drew & Gidding 1982, Shlosman & Vitello 1993, Murray et al 1995, Fukumura et al 2018. Στον αντίποδα συναντάμε τα μοντέλα πυκνωμάτων (clumpy wind models) σύμφωνα με τα οποία οι BALs είναι το προϊόν μιας εκροής η οποία δεν είναι ομαλή και ομοιογενής αλλά στο εσωτερικό της αναπτύσσονται επιμέρους δομές πλάσματος οι οποίες καλούνται νέφη, συμπυκνώσεις, πυκνώματα (Turnshek 1984b;Lyratzi et al 2009Lyratzi et al , 2010cLyratzi et al , 2011Hamann et al 2013;Takeuchi et al 2013Takeuchi et al , 2014Capellupo et al 2012Capellupo et al , 2014Misawa et al 2014Misawa et al , 2016, Stathopoulos et al 2015, Stathopoulos et al , 2017Moscibrodzka & Proga 2013;Proga et al 2014;Proga & Waters 2015;Waters & Proga 2016).…”
Section: κεφάλαιοunclassified
See 3 more Smart Citations